Oldguy : Superhero - Trowbridge, William, 1941- (Book collections on Project MUSE., 2016)
Meet Oldguy: your regular aging superhero whose powers have dwindled over the years, and whose very mechanics are seriously fizzling. In seriocomic misadventures, Oldguy valiantly attempts to continue his former heroism in a somewhat wry version of Faulknerian endurance, defeating his enemies time and again--if not through superhuman abilities, then at least by 'outliving the sons-a-bitches.' With comic book-style illustrations, Oldguy inhabits a space all to itself--not strictly a poetry collection, not quite a graphic novel--in a hybrid comic-chapbook sure to visually and aurally delight.